KETERAMPILAN DASAR BERMAIN BOLA VOLI PADA SISWA KELAS V SEKOLAH DASAR - Yudabbirul Arif; Michael Johannes H Louk; Bertolomeus Keko (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
Mini Volleyball Playing Skills Grade V SD Negeri Malawaru students are still lacking in relation to basic volleyball skills. This is influenced by several factors, namely the allocation of time for learning the game of volleyball which is small, the facilities and infrastructure that are less supportive. This certainly affects the lack of motivation of students in participating in Physical Education learning. Physical education learning process still requires guidance from Physical Education teachers and the lack of basic skills playing volleyball in students in Physical Education subjects. This study aims to determine the level of basic skills playing mini volleyball in grade V SDN Malawaru. This type of research is descriptive research. The research subjects used were 10 grade students of SDN Malawaru. Retrieval of data using observation, interviews and documentation. The data analysis technique uses descriptive analyst, which is outlined in the form of observations. The results showed that the basic skills level of playing mini volleyball in class V SDN Malawaru. It must continue to be improved so that it can produce superior seeds who are skilled in playing volleyball if it is improved since elementary school age